Enhancing User Experiences of Mobile-Based Augmented Reality via Spatial Augmented Reality: Designs and Architectures of Projector-Camera Devices - Thitirat Siriborvornratanakul (Advances in Multimedia)
As smartphones, tablet computers, and other mobile devices have continued to dominate our digital world ecosystem, there are many industries using mobile or wearable devices to perform Augmented Reality (AR) functions in their workplaces in order to increase productivity and decrease unnecessary workloads. Mobile-based AR can basically be divided into three main types: phone-based AR, wearable AR, and projector-based AR. Among these, projector-based AR or Spatial Augmented Reality (SAR) is the most immature and least recognized type of AR for end users. This is because there are a small number of commercial products providing projector-based AR functionalities in a mobile manner. Also, prices of mobile projectors are still relatively high. Moreover, there are still many technical problems regarding projector-based AR that have been left unsolved. Nevertheless, it is projector-based AR that has potential to solve a fundamental problem shared by most mobile-based AR systems. Also the always-visible nature of projector-based AR is one good answer for solving current user experience issues of phone-based AR and wearable AR systems. Hence, in this paper, we analyze what are the user experience issues and technical issues regarding common mobile-based AR systems, recently widespread phone-based AR systems, and rising wearable AR systems. Then for each issue, we propose and explain a new solution of how using projector-based AR can solve the problems and/or help enhance its user experiences. Our proposed framework includes hardware designs and architectures as well as a software computing paradigm towards mobile projector-based AR systems. The proposed design is evaluated by three experts using qualitative and semiquantitative research approaches.